2023
DOI: 10.46838/spr.v4i1.251
|View full text |Cite
|
Sign up to set email alerts
|

Keterampilan Teknik Dasar Renang Gaya Bebas (Crawl) Di SMPN 5 Karawang Barat : Ekspektasi vs Realita

Abstract: Penelitian ini bertujuan untuk mengevaluasi kemampuan renang gaya bebas dasar pascapandemi di SMPN 5 Karawang Barat. Penelitian ini menggunakan metode penelitian deskriptif kuantitatif dan pendekatan penelitian survey. Enam siswa (20%) masuk dalam kategori sangat baik, tiga siswa (10%) masuk dalam kategori baik, enam siswa (20%) masuk dalam kategori cukup, dan enam siswa (20%) masuk dalam kategori baik, sesuai dengan temuan penelitian. 90% siswa termasuk kelompok yang sangat malang, sementara 9% termasuk dalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This means that varied training methods with smaller class sizes have a significant effect on students' front crawl swimming skills. The findings do not support the contextual interference effect (CIE) because when practice schedules are manipulated, as in the blocked and random schedules, the basis for establishing different levels of contextual interference becomes the presentation of the variations themselves (Dira Fauzi et al, 2023;Rezki et al, 2019). However, it is found that varied training of blocked practice followed by serial practice or random practice, even when combined, can produce better learning than exercises done only in blocked practice, serial practice, or random practice.…”
Section: Discussionmentioning
confidence: 97%
“…This means that varied training methods with smaller class sizes have a significant effect on students' front crawl swimming skills. The findings do not support the contextual interference effect (CIE) because when practice schedules are manipulated, as in the blocked and random schedules, the basis for establishing different levels of contextual interference becomes the presentation of the variations themselves (Dira Fauzi et al, 2023;Rezki et al, 2019). However, it is found that varied training of blocked practice followed by serial practice or random practice, even when combined, can produce better learning than exercises done only in blocked practice, serial practice, or random practice.…”
Section: Discussionmentioning
confidence: 97%